Given:
There are given that the function:
![f(x)=(x-19)^2](https://img.qammunity.org/2023/formulas/mathematics/high-school/9bf0w1ji1phoky6tj523fcgnj3dv88psqm.png)
Step-by-step explanation:
According to the question:
We need to find the inverse of the function.
Then,
To find the inverse, first exchange f(x) into y:
So,
![\begin{gathered} f(x)=(x-19)^(2) \\ y=(x-19)^2...(1) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/f1g48zyg7o3zr1it4agpi3i6gq3cophn30.png)
Then,
We need to exchange x into y:
So,
![\begin{gathered} y=(x-19)^2 \\ x=(y-19)^2...(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/te9mljm7rrw0n7n0gg4b94ybvatuwnk4y0.png)
Then,
We need findthe value for y:
![\begin{gathered} \begin{equation*} x=(y-19)^2 \end{equation*} \\ \pm√(x)=y-19 \\ y=\pm√(x)+19 \\ y=√(x)+19,-√(x)+19 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/tfiniglsp1frqw0p1k3n3g84nk5x9p331b.png)
Then,
![f^(-1)(x)=√(x)+19,-√(x)+19](https://img.qammunity.org/2023/formulas/mathematics/high-school/e62fd5i23bc86ixvi0gjm8wjw4ccw2jx55.png)
Final answer:
Hence, the inverse of the given function is show below:
![f^(-1)(x)=√(x)+19](https://img.qammunity.org/2023/formulas/mathematics/high-school/wks81dcqi7qv9496emilnsly6digyslbdw.png)